Cyclin A2 modulates EMT via β-catenin and phospholipase C pathways. (19th May 2015) - Cheung, Caroline T.; Bendris, Nawal; Paul, Conception; Hamieh, Abdallah; Anouar, Youssef; Hahne, Michael; Blanchard, Jean-Marie; Lemmers, Bénédicte
Summary: Cyclin A2 depletion induces EMT through β-catenin activation via phospholipase C. This process is reversed by the use of a dominant negative form of TCF4 which inhibits β-catenin transcriptional activity as well as by inhibiting phospholipase C using U7312 (1 ). Abstract : We have previously demonstrated that Cyclin A2 is involved in cytoskeletal dynamics, epithelial-mesenchymal transition (EMT) and metastasis. This phenotype was potentiated by activated oncogenic H-Ras. However, the mechanisms governing EMT in these cells have not yet been elucidated. Here, we dissected the pathways that are responsible for EMT in cells deficient for Cyclin A2. In Cyclin A2-depleted normal murine mammary gland (NMuMG) cells expressing RasV12, we found that β-catenin was liberated from the cell membrane and cell–cell junctions and underwent nuclear translocation and activation. Components of the canonical wingless (WNT) pathway, including WNT8b, WNT10a, WNT10b, frizzled 1 and 2 and TCF4 were upregulated at the messenger RNA and protein levels following Cyclin A2 depletion. However, suppression of the WNT pathway using the acetyltransferase porcupine inhibitor C59 did not reverse EMT whereas a dominant negative form of TCF4 as well as inhibition of phospholipase C using U73122 were able to do so. This suggests that a WNT-independent mechanism of β-catenin activation via phospholipase C is involved in the EMT induced by Cyclin A2 depletion. Our findings will broaden our knowledge on how Cyclin A2 contributes to EMT and metastasis.